2022
DOI: 10.3389/fcimb.2022.1047607
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome in young women at different stages of periodontitis: Prevotella dominant in stage III periodontitis

Abstract: ObjectivePeriodontitis progression is related to the dynamic dysbiosis of oral microbiome. We identified the dominant bacteria and the potential pathway in young women with stage-III periodontitis.Materials and methodsSamples of subgingival plaque were collected from 26 young women with periodontitis (20 with stage-I and 6 with stage-III). Using 16S rRNA-sequencing, we determined the variation in oral bacterial communities of the two groups, and identified the dominant bacteria of each group. We used the Kyoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Gut microbes influence both local and systemic immunity (32). The gut microbiome regulates, optimizes, and suppresses host immune responses, and these changes allow infectious diseases to gain the upper hand (33,34). Recent studies have linked an increase in intestinal microbiota Prevotella at mucosal sites to local and systemic inflammation (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes influence both local and systemic immunity (32). The gut microbiome regulates, optimizes, and suppresses host immune responses, and these changes allow infectious diseases to gain the upper hand (33,34). Recent studies have linked an increase in intestinal microbiota Prevotella at mucosal sites to local and systemic inflammation (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The SILVA database is a comprehensive web resource for upto-date, quality-controlled databases of aligned rRNA gene sequences from the Bacteria, Archaea and Eukaryota domains (Quast et al, 2013). Several previous studies have also used the SILVA database for oral microbiome analysis (Kennedy et al, 2016;Zhao et al, 2021;Zhao et al, 2022). Furthermore, a recent systematic review of oral peri-implant and periodontal microbiota (Gazil et al, 2022) showed a specific database for oral microbiomes, such as the HOMD (Chen et al, 2010) (https://www.homd.org/).…”
Section: Discussionmentioning
confidence: 99%
“…A higher abundance of members of the Prevotellaceae family in the oral cavity predicted SARS-CoV-2 infection in the pregnant cohort included in this study. Members of this bacteria family, such as P. intermedia , are considered the main bacterial species implicated in periodontitis [ 61 ]. Similarly, H. parainfluenzae , an oral commensal associated with beneficial immunomodulatory effects, is decreased in the pregnant women with SARS-CoV-2 included in this study [ 62 ].…”
Section: Discussionmentioning
confidence: 99%